A retrospective cross-sectional study on the prevalence of hypodontia in a target population of Al-Jouf Province, Saudi Arabia - Arbaz Sajjad; Samia Subhani Sajjad; Nadeem Husain; Ahmed Maashi Al-Enezi (Wolters Kluwer Medknow Publications, 2016)
Aim: The purpose of this retrospective study was to determine the prevalence of hypodontia and to ascertain the need of interdisciplinary treatment for ensuing esthetic and functional problems in a target population of Al-Jouf Province, Saudi Arabia. Subjects and Methods: Using a dental administration software tool, a total of 1267 patients who presented to the outpatient clinics of the Orthodontic and Prosthodontic Departments between March 2015 and January 2016 were identified. Of those, 694 were females and 573 were males. All permanent teeth were investigated, except third molars. Results: The prevalence of hypodontia was 6.1%. The difference between genders was not statistically significant (P = 0.597) although female hypodontia prevalence was higher than males (6.6% and 5.5%, respectively). The majority of patients had one or two missing teeth. There were no significant differences between right and left sides for any particular tooth. The most commonly missing teeth were mandibular second premolar (40.1%), followed by the maxillary lateral incisor (20.4%) and then the maxillary second premolars (12.6%). Conclusions: The prevalence of hypodontia in Al-Jouf Province, Saudi Arabia, was within the average values portrayed in the majority of the published literature. The majority of affected individuals had one or two missing teeth. None of the patients examined had more than four missing teeth. There were no significant differences in the distribution of hypodontia between the affected jaws according to gender. Although less prevalent, considerable cases of bilateral missing teeth were found in the present study which necessitates the need for urgent interdisciplinary intervention and management.